Realisasi Merdeka Belajar dengan Menggunakan Strategi Pembelajaran Diferensiasi Proses pada Siswa SMA Kelas X - Wijayanti, Dyah Ayu; Prihandini, Dwi Rani (Indonesian Journal Publisher, 2024)
Centered learning on the teacher is considered ineffective in education today. The role of a teacher is not just to transfer knowledge, but also to facilitate students in connecting with their learning resources to achieve meaningful learning. Therefore, teaching and learning activities are less optimal if conducted in only one direction. In line with the new paradigm of learning, teachers must be able to continuously innovate and be creative in delivering student-centered learning. One implementation of student-centered learning is through differentiated learning. The aim of this research is to describe the implementation of the process differentiation learning strategy for grade 10 students. The method used is qualitative descriptive with data collection strategies through direct observation and questionnaires. The research was conducted at SMAN Rambipuji with the research subjects being all grade 10 students. The process differentiation learning strategy is implemented successfully. The research findings show that the implementation of the process differentiation learning strategy is used by teachers as a guide to deliver student-centered learning.